Social Network Mapping and Functional Recovery Within 6 Months of Ischemic Stroke. (November 2019) - Dhand, Amar; Lang, Catherine E.; Luke, Douglas A.; Kim, Angela; Li, Karen; McCafferty, Liam; Mu, Yi; Rosner, Bernard; Feske, Steven K.; Lee, Jin-Moo
Objective. Stroke recovery is a multidimensional process influenced by biological and psychosocial factors. To understand the latter, we mapped the social networks of stroke patients, analyzing their changes and effects on physical function at 3 and 6 months after stroke. Methods. We used a quantitative social network assessment tool to map the structure and health habits embedded in patients' personal social networks. The physical function outcome was determined using the National Institutes of Health (NIH) Patient-Reported Outcomes Measurement Information System (PROMIS) Physical Function Scale (0-100, mean 50 for US general population). We used mixed-effects models to assess changes in social network metrics. We used multivariable models to test the association between social networks and physical function, independent of demographics, socioeconomic status, clinical characteristics, comorbidities, cognition, and depression. Results. The cohort consisted of 172 patients, with mostly mild motor-predominant stroke (median NIH Stroke Scale of 2) with retention of 149 at 3 months and 139 at 6 months. An average patient's network over 6 months contracted by 1.25 people and became denser and family oriented. Network composition also became healthier with pruning of ties with people who smoked or did not exercise. The baseline network size, and not density or health habits in the network, was independently associated with 3- and 6-month physical function PROMIS scores. Patients embedded in small kin-based networks reported more negative social interactions. Conclusions. Despite social networks becoming smaller and close-knit after stroke, they also become healthier. Larger baseline social networks are independently associated with better patient-reported physical function after stroke.